2019
DOI: 10.33094/26410249.2019.14.82.86
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Intention towards Halal Food in Low-Cost Airlines in Kelantan, Malaysia

Abstract: Low cost airline is the airline that excluding many traditional passenger services and offers generally low fares in exchange. In-flight meal is one of the services that being offered in the low-cost airlines, but the passenger must pay for it. The acceptation of halal food in Malaysia is still low compared to neighbouring country. This study is aimed to identify the intention's level of consumers and the relationship between religion and consumers intention towards Halal food in low-cost airlines. A self-admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…These customers are actively committed to or aware of their intention to acquire environmentally friendly goods [7]. There are a plethora of studies that have been conducted worldwide on pro-environmental behavior [17][18][19][20][21][22], green consumption [23][24][25][26], the purchase of eco-labeled products [27,28] and organic foods [29][30][31][32], that focus as well on various other types of green products as research objectives. However, studies on green buying behavior are limited in South Asian countries (Table 1), as only a few studies have been acknowledged from India [33][34][35][36][37][38], Pakistan [39], and Sri Lanka [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…These customers are actively committed to or aware of their intention to acquire environmentally friendly goods [7]. There are a plethora of studies that have been conducted worldwide on pro-environmental behavior [17][18][19][20][21][22], green consumption [23][24][25][26], the purchase of eco-labeled products [27,28] and organic foods [29][30][31][32], that focus as well on various other types of green products as research objectives. However, studies on green buying behavior are limited in South Asian countries (Table 1), as only a few studies have been acknowledged from India [33][34][35][36][37][38], Pakistan [39], and Sri Lanka [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated a few variables that influence purchase intention among people. According to Latiff et al (2019), purchasing behavioural intention is influenced by awareness, knowledge, attitude, as well as food labels. Meanwhile, Vanany et al (2019) found that attitude has a significant effect toward purchase intention on halal food, whereas subjective norms, perceived behavioural control and halal awareness have insignificant effect toward purchase intention.…”
Section: Literature Review Purchase Intentionmentioning
confidence: 99%